Evaluation of Cardiovascular Outcomes in Adult Patients With Episodic or Chronic Migraine Treated With Galcanezumab: Data From Three Phase 3, Randomized, Double‐Blind, Placebo‐Controlled EVOLVE‐1, EVOLVE‐2, and REGAIN Studies - Oakes, Tina M.; Kovacs, Richard; Rosen, Noah; Doty, Erin; Kemmer, Phebe; Aurora, Sheena K.; Camporeale, Angelo (Headache, 2020)
Objective Blood pressure (BP), pulse, electrocardiogram (ECG), and clinical cardiovascular (CV) outcomes in patients with episodic or chronic migraine treated for up to 6 months with galcanezumab compared to placebo were evaluated. Background Calcitonin gene‐related peptide, a potent microvascular vasodilator, has a hypothesized protective role in CV health. Increased CV risks have been reported in patients with migraine. Methods In 2 similarly designed episodic migraine 6‐month studies and 1 chronic migraine 3‐month study, data from patients randomized (1:1:2) to subcutaneous injection of galcanezumab 120 mg/month (following initial 240 mg loading dose) or 240 mg/month or placebo were pooled. Treatment comparisons for cardiovascular treatment‐emergent adverse events (CV TEAE) and categorical and mean changes in BP, pulse, and ECG were evaluated using the Cochran‐Mantel‐Haenszel test. Mean changes from baseline in BP, pulse, and ECG were evaluated using the analysis of covariance model. Results Overall, among galcanezumab 120 mg (n = 705) and 240 mg (n = 730), and placebo (n = 1451) groups, the percentage of patients reporting ≥1 CV TEAE was low and was similar between the galcanezumab 120 mg (2.6%; odds ratio [OR] = 0.9; 95% confidence interval [CI]: 0.5,1.5) and galcanezumab 240 mg (3.3%; OR = 1.1; 95% CI: 0.7,1.9), and placebo (2.9%) groups. The frequency of any individual CV TEAE, broad or narrow term, was ≤1.4%. The CV‐related serious adverse events that occurred in the galcanezumab 240 mg group (n = 3; acute myocardial infarction, pulmonary embolism, and transient ischemic attack) and placebo group (n = 3; pulmonary embolism, deep vein thrombosis, and myocardial infarction) were not considered treatment related. Four placebo‐ and 1 galcanezumab‐treated patient discontinued due to a CV TEAE. Least squares mean and categorical changes from baseline in BP, pulse, and QT interval corrected using Fridericia’s correction were similar across treatment groups. Conclusions In this 6‐month treatment trial, the percentages of galcanezumab‐ and placebo‐treated patients that reported CV TEAEs or serious adverse events were low and similar between groups with few discontinuations. Thus, no clinically meaningful treatment group differences were observed for changes in BP, pulse, or ECG parameters. Additional longer‐term studies in a broader and larger cohort are required to better characterize CV safety.